2003
DOI: 10.1159/000073366
|View full text |Cite
|
Sign up to set email alerts
|

Ifosfamide in the Adjuvant Therapy of Soft Tissue Sarcomas

Abstract: Ifosfamide and anthracyclines are the only active agents in advanced soft tissue sarcomas. Doxorubicin was always used in sarcomas, whereas ifosfamide was reintroduced in the clinic after the discovery of mesna which prevents its typical dose-limiting toxicity: hemorrhagic cystitis. In the adjuvant setting, doxorubicin was used alone or in combination in the first-generation trials, whereas its parent compounds epirubicin and ifosfamide were employed in the second-generation adjuvant trials, which started in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
88
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(99 citation statements)
references
References 7 publications
8
88
0
3
Order By: Relevance
“…From our survival analysis, the median follow-up period was 51 months, which is similar to durations of follow-up reported in previous studies [7][8][9][10][11][12][13][14][15][16][17] . Overall median DFS was 33 months in our study population.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…From our survival analysis, the median follow-up period was 51 months, which is similar to durations of follow-up reported in previous studies [7][8][9][10][11][12][13][14][15][16][17] . Overall median DFS was 33 months in our study population.…”
Section: Discussionsupporting
confidence: 85%
“…This 4-week period is comparable to the reported 4-week time frame within which chemotherapy was commenced in several previous studies [7][8][9][10][11][12][13][14] . We found tumor grade 3 with size >10 cm showed a non-significant trend toward association with worse OS.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…One theory regarding how chemotherapy might affect local control is that chemotherapy may affect actively dividing cells at the margins of tumors [19]. Although controversy remains regarding the topic with several articles failing to show an effect on local control [6,7,18], other studies have shown that chemotherapy could benefit patients with sarcoma in terms of better local relapse-free survival and overall survival [9,10,13,21]. The effects could be dependent on the exact agents and dosages.…”
Section: Discussionmentioning
confidence: 99%
“…One of its most important uses is in advanced soft tissue sarcomas where it is used as adjuvant chemotherapy along with doxorubicin [2,3]. The Italian cooperative trial showed 5-year overall survival estimate to be 66.0% and 46.1% for the treatment and the control groups, respectively (p=0.04) [4]. Ifosfamide and doxorubicin are also used with good results in advanced rhabdomyosarcoma.…”
Section: Introductionmentioning
confidence: 99%